Wheat seed quality under conservation agriculture system - ASHWANI KUMAR; ANIL KHIPPAL; RAM NIWAS YADAV; H. PRASHANTH BABU (Seed Research, 2026)
Wheat seed yield and seed quality was studied under conservation agriculture systemconsisting of six tillage combinations viz., RT-DSR-ZTW (Reduced till Direct seeded rice fb Zero tillage wheat), RT-DSR-ZTW-Sesbania, PUTPR (Puddled transplanted rice) - Reduced till wheat, PUTPR- Rotavator wheat, RT-DSR-ZTW+Rice residue and UPTPR (Unpuddled transplanted rice)-ZTW+Rice residue under rice-wheat cropping system at Krishi Vigyan Kendra, Kaithal in 2010-11 and 2011-12. Treatment RT-DSR-ZTW+Rice residue and UPTPR-ZTW+Rice residue performed significantly better than all other treatments for seed yield and seed quality attributes viz., standard germination, speed of germination, vigour index-I & II in 2010-11; these treatments have significantly outperformed PUTPR- Reduced till wheat and PUTPR-Rotavator wheat, the tillage techniques most commonly followed for seed production in wheat. The crop residues retained as surface mulch in RT-DSR-ZTW+Rice residueand UPTPR-ZTW+Rice residue would have helped in regulating the soil temperature, moisture and organic carbon in 2010-11. The greater yield response was mainly due to the cooler weather conditions during the grain filling period and all the treatments were at par for seed yield in 2011-12. Treatments RT-DSR- ZTW, RT-DSR-ZTW-Sesbania, RT-DSR-ZTW+Rice residue and UPTPR-ZTW+Rice residue performed significantly better than PUTPR-Reduced till wheat and PUTPR-Rotavator wheat for seed quality parameters except germination.